Loose Women Girls' Night in : Heartfelt Advice, Inspired Innuendo and Toe-Curling Confessions (London Hodder & Stoughton, 2009)
Hit ITV show Loose Women has been delivering daily lunchtime treats for a decade now, to a loyal audience of over a million viewers. This book is packed with wickedly funny stories and outspoken opinions from the show's feisty panellists.
Include Illustrations
Keywords: Man-woman relationships